Effects of two low-volume high-intensity interval training protocols in professional soccer: sprint interval training versus small-sided games - Boraczynski, M. T.; Laskin, J. J.; Gajewski, J.; Podstawski, R. S.; Brodnicki, M. A.; Boraczynski, T. W. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: The programming of training protocols within a high-intensity interval training (HIIT) framework with appropriate analysis of total training load could deliver optimal training adaptations. This study aims to compare the efficiency of two low-volume HIIT protocols integrated with the regular training regime in professional soccer players. METHODS: Twenty-five participants aged 18.4-29.7 years were randomly assigned to one of two interventions involving straight-line sprint interval training (SIT, N.=13) or small-sided games (SSG, N.=12). Periodization was divided into two 3-week phases concluded by a 7-day taper. SIT first involved two-session·week-1 of one set of 10·45-s sprints (at maximal intensity) and then three-session·week-1 of two sets of 10·30-s sprints with a 0.75:1 and 1:1 recovery interval (slow running and stretching exercises), respectively. SSG in the first phase involved 5·3-min games of 4 vs. 4 and in the second phase 4·4-min games of 2 vs. 2 with 3-min recovery (practice drills at 60-70% HRmax). Training load was controlled via session-RPE and HR-based methods. Pre- and postintervention testing included: countermovement jump height, 5-m and 30-m sprints performance, anaerobic power by the 10-s Wingate Anaerobic Test, maximal oxygen uptake (VO2max) and blood lactate concentration (BLa-) determined by incremental exhaustive running test. RESULTS: Two-way ANOVA showed group×time interaction effects for the 30-m sprint time (F(1,23)=3.023; P=0.049; ?2 P=0.116), BLa- (F(1,23)=5.250; P=0.031; n2 P=0.185), and VO2max (F(1,23)=4.648, P=0.044; n2 P=0.157). SIT elicited greater enhancements in anaerobic performance (30-m sprint time and BLa-), while SSG induced larger improvements in VO2max. CONCLUSIONS: Comparable effects of SIT and SSG protocols were noted, however the aerobic capacity benefits provided by SSG warrant this HIIT protocol as a highly recommended training modality in the professional soccer.